2014
DOI: 10.1186/1472-6750-14-37
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco BY-2 cell-free lysate: an alternative and highly-productive plant-based in vitro translation system

Abstract: BackgroundCell-free protein synthesis is a rapid and efficient method for the production of recombinant proteins. Usage of prokaryotic cell-free extracts often leads to non-functional proteins. Eukaryotic counterparts such as wheat germ extract (WGE) and rabbit reticulocyte lysate (RLL) may improve solubility and promote the correct folding of eukaryotic multi-domain proteins that are difficult to express in bacteria. However, the preparation of WGEs is complex and time-consuming, whereas RLLs suffer from low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 49 publications
2
59
0
Order By: Relevance
“…We started with magnesium concentration, which is known to be a fundamentally important physicochemical salt used in cell-free systems that influences the functional activity of the translation apparatus (Jewett et al, 2008;Klein et al, 2004;Liiv and O'Connor, 2006;Yamamoto et al, 2010). Previous reports have shown that the optimal Mg 2þ concentrations in different CFPS systems are also different, for example, E. coli (12 mM) (Jewett and Swartz, 2004a), yeast (7 mM) (Hodgman and Jewett, 2013), Bacillus subtilis (15 mM) (Zaghloul and Doi, 1987), PURE system (9 mM) (Shimizu et al, 2001), wheat germ extract (2.5 mM) (Marcu and Dudock, 1974) and tobacco BY-2 extract (1.44 mM) (Buntru et al, 2014). Although the early study reported that 12 mM of Mg 2þ was optimal for the Streptomyces cell-free system (Thompson et al, 1984), we decided to re-examine the magnesium ion concentration.…”
Section: Optimization Of Cell-free Reaction Conditionsmentioning
confidence: 99%
“…We started with magnesium concentration, which is known to be a fundamentally important physicochemical salt used in cell-free systems that influences the functional activity of the translation apparatus (Jewett et al, 2008;Klein et al, 2004;Liiv and O'Connor, 2006;Yamamoto et al, 2010). Previous reports have shown that the optimal Mg 2þ concentrations in different CFPS systems are also different, for example, E. coli (12 mM) (Jewett and Swartz, 2004a), yeast (7 mM) (Hodgman and Jewett, 2013), Bacillus subtilis (15 mM) (Zaghloul and Doi, 1987), PURE system (9 mM) (Shimizu et al, 2001), wheat germ extract (2.5 mM) (Marcu and Dudock, 1974) and tobacco BY-2 extract (1.44 mM) (Buntru et al, 2014). Although the early study reported that 12 mM of Mg 2þ was optimal for the Streptomyces cell-free system (Thompson et al, 1984), we decided to re-examine the magnesium ion concentration.…”
Section: Optimization Of Cell-free Reaction Conditionsmentioning
confidence: 99%
“…152 In practice, however, only a few cell-free systems have been developed for in vitro protein synthesis. In general, these systems are derived from cells engaged in a high rate of protein synthesis, and commercially available systems exist for various applications including ribosome display and unnatural amino acid incorporation.…”
Section: Cell-free Translation: a Dizzying Scaling-upmentioning
confidence: 99%
“…Established eukaryotic systems include yeast [18], wheat germ [19,20], insect [21,22], tobacco [23] and mammalian [24,25] cell lysates. The wheat germ system is highly popular due to its high yields, but limited in regard to the correct post-translational modification of human proteins.…”
Section: Introductionmentioning
confidence: 99%